Pojęcie identyfikacji w naukach społecznych - Radziewicz-Winnicki, Andrzej (Wydział Prawa i Administracji UAM, 1989)
The aim of the article is to present three ways of interpreting the concept of "identification" used in social sciences writing. The article offers examples of interpretation by psychologists, sociologists and educationists. The author starts with the uses of the said concept in selected theories of marxism and interactionism. Despite different ways of interpretation, various authors arrive at conclusions which often lead to the same basic statement, i.e. to a conviction that an individual always strives to satisfy his/her own needs. If his/her actions are efficient (i.e. if they are successful or if they meet the expectations of an individual), then the appearance of identification processes with another person, a social group or a system of values becomes more probable.
The concept of identification in social sciences